Fluoroquinolone resistance in Escherichia coli isolates after exposure to non-fluoroquinolone antibiotics: a retrospective case–control study. (12th May 2020) - Chaname Pinedo, Linda E; Bruyndonckx, Robin; Catry, Boudewijn; Latour, Katrien; Goossens, Herman; Abrams, Steven; Coenen, Samuel
Abstract: Objectives: To investigate whether prior exposure to non-fluoroquinolone antibiotics increases the risk of fluoroquinolone resistance in Escherichia coli . Methods: This was a secondary analysis of data collected retrospectively in a case–control study linking microbiological test results (isolated bacteria and their susceptibility) of urine samples routinely collected from primary, secondary and tertiary care patients in Belgium with information on prior antibiotic use at the patient level up to 1 year previously. Results: In urine samples from 6125 patients, 7204 E. coli isolates were retrieved [1949 fluoroquinolone-resistant isolates (cases) and 5255 fluoroquinolone-susceptible isolates (controls)]. After adjusting for potential confounders (including fluoroquinolone use) and correcting for multiple testing there were lower odds of fluoroquinolone resistance in E. coli isolates after exposure to cefazolin (OR = 0.65; 95% CI = 0.52–0.81; P = 0.00014) and higher odds after exposure to trimethoprim/sulfamethoxazole (OR = 1.56; 95% CI = 1.23–1.97; P =0.00020) or nitrofurantoin (OR = 1.50; 95% CI = 1.23–1.84; P =0.000083). A sensitivity analysis excluding samples with antibiotic use during the 6 months prior to the sampling date confirmed the higher odds of fluoroquinolone resistance after exposure to trimethoprim/sulfamethoxazole and nitrofurantoin. Conclusions: Assuming no residual confounding or other biases, this study suggests that exposure to non-fluoroquinolone antibiotics, i.e. trimethoprim/sulfamethoxazole and nitrofurantoin, might be causally related to fluoroquinolone resistance in E. coli isolates from urinary samples. Future prospective research is needed to confirm non-fluoroquinolone antibiotics as potential drivers of fluoroquinolone resistance.